Real-world 12-month outcomes of repeated high-concentration capsaicin patch in chemotherapy-induced peripheral neuropathy: results from the CASPAR study - Überall, Michael A.; Sabatowski, Rainer; Lux, Michael Patrick; Heine, Myriam; Garcia Guerra, Lucia; Eerdekens, Mariëlle; Quandel, Tamara (Frontiers in Oncology, 2025)
BackgroundChemotherapy-nduced peripheral neuropathy (CIPN) is a frequent and debilitating complication of cancer therapy, often leading to chronic pain, impaired quality of life (QoL), and reduced daily functioning. This study evaluated the long-term effectiveness and safety of repeated high-concentration capsaicin patch (HCCP) treatment for CIPN using real-world data from the German Pain e-Registry (GPeR).MethodsIn this retrospective, observational, non-randomized cohort study, 169 CIPN patients who received one to four HCCP treatments were followed at 3-monthly intervals (± 2 weeks) over 12 months. Assessed outcomes included average 24-hour pain intensity (API), QoL, sleep, emotional well-being, daily functioning, analgesic use, and safety.ResultsOf 169 patients, 65 received one, 35 two, 25 three, and 44 four treatments. At month 12, patients receiving four treatments showed a marked API reduction on the 0–100 mm VAS scale (from 55.9 mm to 17.3 mm), compared to a minimal change in the one-treatment group (56.9 mm to 53.2 mm). A ≥30% API reduction was achieved in 20.0%, 54.3%, 76.0%, and 97.7% of patients receiving one to four treatments, respectively. Clinically meaningful improvements were also observed in sleep, QoL, emotional distress, and functional capacity, along with a decline in analgesic use. While continued treatment was associated with cumulative benefits, early discontinuation was consistently linked to symptom recurrence. Adverse events were mostly mild, transient, and limited to the application site.ConclusionThis real-world analysis indicates that repeated HCCP treatment is associated with progressive improvements in pain intensity, QoL, and functional outcomes in patients with CIPN, while maintaining good long-term tolerability.